2018
DOI: 10.25300/misq/2018/13490
|View full text |Cite
|
Sign up to set email alerts
|

Platform Sponsor Investments and User Contributions in Knowledge Communities: The Role of Knowledge Seeding

Abstract: How should digital platforms engage with and invest in their online communities to shape innovation and knowledge contributions from members in their platform ecosystems? This is an important question because user contributions are important drivers of technological progress and business value. We examine the effect of platform sponsors' investments in online communities on user knowledge contributions, using fine-grained longitudinal data from a leading enterprise software vendor's community network. We focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(50 citation statements)
references
References 92 publications
1
48
0
Order By: Relevance
“…In fact, several authors had already outlined the role of the leader users (Von Hippel, 1986;Morrison et al, 2000;Morrison et al, 2004;Franke et al, 2006;Jeppesen and Laursen., 2009). It was even established that there is an increase in contributions from users when they Huang et al (2018) did, we identified that the knowledge spreading process is a cause of major knowledge contributions to the platform, and also of increased trust between users.…”
Section: Structurementioning
confidence: 84%
See 2 more Smart Citations
“…In fact, several authors had already outlined the role of the leader users (Von Hippel, 1986;Morrison et al, 2000;Morrison et al, 2004;Franke et al, 2006;Jeppesen and Laursen., 2009). It was even established that there is an increase in contributions from users when they Huang et al (2018) did, we identified that the knowledge spreading process is a cause of major knowledge contributions to the platform, and also of increased trust between users.…”
Section: Structurementioning
confidence: 84%
“…A critical part of the platform to promote the commitment of the user is the support provided by a "cognitive assistant". The key factors to develop the user knowledge contributions with an online community are, on the one hand, their predisposition to share with others, and on the other hand, their ability to contribute to collective knowledge (Huang et al, 2018). To improve both, the studied platform invites acknowledged leaders of the subject to be cognitive assistants or according to Arena et al (2017) "central connectors".…”
Section: Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, retailers with marketing budgets offering horizontally differentiated products (like apparel with different colors or food products with different flavors) have greater incentives to cooperate with social media platforms (e.g. Instagram and Pinterest) in targeting influential customers (Huang et al 2018). For example, after finishing an online transaction, online retailers can encourage influential customers of such products to share their purchases via social media through a discount scheme (the discount scheme can be a simple percent discount or be based on consumer contests, see Liu et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…[74] One online brand community: Dell's IdeaStorm Delivering (swift) firm feedback Delivering (swift) feedback by the community host encourages the community members to contribute. [75] One online knowledge community: SAP Knowledge seeding Knowledge seeding strategies induced by the hosting firm positively impacts the community's knowledge contributions.…”
Section: Appendix a Literature Review Of Firm Initiatives To Stimulamentioning
confidence: 99%